MEASUREMENT OF PHYSICAL ROCK PROPERTIES AND SELECTION OF IDENTIFIED CORE PLUGS FOR INJECTIVITY AND BLOCKING TESS - Nuraini Nuraini (Testing Center for Oil and Gas LEMIGAS, 2005)
An oil field on the island of Sumatra in Indonesia has excess water production problem. Its watercuts are greater than 90 %. Excess water production is not only linked to poor sweep efficiency, but also causes many problems in oil industry, such as scaling, corrosion, cost of oil water treatment and cost of water disposal, and in effective hydrocarbon mobility. Optimizing oil production often requires considerable time, effort and challenge. Chemical injection (e.g. BW Polymer) is a method proposed to solve the current problem in the oil field. Hopefully, the excess water production will be blocked effectively by using chemical injection method in order to obtain maximum productivity and recovery. This paper is especially focused on measurement of physical rock properties, identification and selection of core plugs for injectivity and blocking test study